An Analysis of Verbal and Visual Signs Meaning Found in Azarine Sunscreen Advertisement - Ni Kadek Windy Adnyani; Putu Gede Budiartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The study entitled “An Analysis of Visual and Verbal Signs Meaning Found in Azarine Sunscreen Advertisement” aims to analyze and identify the verbal and visual signs as well as their meanings. Used social media advertisement plays an important role in promoting and encouraging their product to the audience. In this research, the data was taken from Azarine Instagram advertisements @azarinecosmeticofficial. The data was collected by observation method and analyzed in descriptive qualitative method. This research used the theory from Saussure (2011) to analyze the verbal and visual signs and the theory from Bathes (1977) to interpret their meanings. The findings identified 7 verbal signs and 13 visual signs that convey denotative and connotative meanings. As the results of this research, the verbal signs in this advertisement appeared in text and always showed their brand name “Azarine” which enhanced the product’s visibility and credibility, making it more recognizable to the audience. The visual signs appeared in pictures, elements, repetition of several logos which reinforce the brand dedication and commitment to meet audience needs, and backgrounds with the identic colors of blue and orange which are eye-catching and could attract the attention of the audience when they see Azarine Sunscreen advertisement.